6ху+3у+4х-6ху 3у+4х
--------------------- = ---------------
36 х^2e^2 36х^2y^2
a^2+2a+4a+8-a^2-6a 8
------------------------------ = -----------
a(a+2) a(a+2)
(a+1)^2 - (a-1)^2 a^2+2a+1 -(a^2 -2a+1)
----------------------- = --------------------------------- =
2a(a^2 -1) 2a(a^2 -1)
a^2+2a+1-a^2 +2a -1 4a 2
---------------------------- = ------------ = ------------
2a(a^2-1) 2a(a^2 -1) ( a^2-1)
a - 5 3a +5 a^2-5a +15a+25 (a+5)^2 a+5
------ + ------------ = ------------------------- = -------------- = -------------
5(a+5) a(a+5) 5a(a+5) 5a(a+5) 5a
в первом примере нет ошибки? может быть там минус?
посмотри !!!